Ethiodised Oil Lymphangiography in the Management of Chyluria - Vishal Nandkishor Bakare; Pratiksha Yadav; Krishna Teja Nerella (Journal of Clinical and Diagnostic Research, 2022)
Chyluria is clinical condition in which there is excretion of chyle in urine. The most common cause of chyluria is lymphatic filariasis. This case report describes imaging findings of non filarial chyluria due to retroperitoneal lymphatic cyst and its successful management by minimally invasive percutaneous lymphangiography procedure. The patient presented with complaints of passing milky white urine which was confirmed to be chyluria. After a non successful trial of conservative approach in form of high-protein and low-fat diet, percutaneous ethiodised oil lymphangiography was performed, which resulted in immediate symptomatic improvement and no recurrence on follow-up.